Management of cardiac arrest survivors in UK intensive care units: a survey of practice. (May 2016) - Ford, AH; Clark, T; Reynolds, EC; Ross, C; Shelley, K; Simmonds, L; Benger, J; Soar, J; Nolan, JP; Thomas, M
Background: Cardiac arrest is a common presentation to intensive care units. There is evidence that management protocols between hospitals differ and that this variation is mirrored in patient outcomes between institutions, with standardised treatment protocols improving outcomes within individual units. It has been postulated that regionalisation of services may improve outcomes as has been shown in trauma, burns and stroke patients, however a national protocol has not been a focus for research. The objective of our study was to ascertain current management strategies for comatose post cardiac arrest survivors in intensive care in the United Kingdom. Method: A telephone survey was carried out to establish the management of comatose post cardiac arrest survivors in UK intensive care units. All 235 UK intensive care units were contacted and 208 responses (89%) were received. Results: A treatment protocol is used in 172 units (82.7%). Emergency cardiology services were available 24 hours a day, 7 days a week in 54 (26%) hospitals; most units (123, 55.8%) transfer patients out for urgent coronary angiography. A ventilator care bundle is used in 197 units (94.7%) and 189 units (90.9%) have a policy for temperature management. Target temperature, duration and method of temperature control and rate of rewarming differ between units. Access to neurophysiology investigations was poor with 91 units (43.8%) reporting no availability. Conclusions: Our results show that treatments available vary considerably between different UK institutions with only 28 units (13.5%) able to offer all aspects of care. This suggests the need for 'cardiac arrest care bundles' and regional centres to ensure cardiac arrests survivors have access to appropriate care.